Engineered Soluble Monomeric IgG1 Fc with Significantly Decreased Non-Specific Binding - Wang, Chunyu; Wu, Yanling; Wang, Lili; Hong, Binbin; Jin, Yujia; Hu, Dan; Chen, Gang; Kong, Yu; Huang, Ailing; Hua, Guoqiang; Ying, Tianlei (Frontiers in Immunology, 2017)
Due to the long serum half-life provided by the neonatal Fc receptor (FcRn) recycling, the IgG1 Fc has been pursued as the fusion partner to develop therapeutic Fc-fusion proteins, or as the antibody-derived scaffold that could be engineered with antigen-binding capabilities. In previous studies, we engineered the monomeric Fc by mutating critical residues located on the IgG1 Fc dimerization interface. Comparing with the wild-type dimeric Fc, monomeric Fc might possess substantial advantages conferred by its smaller size, but also suffers the disadvantage of non-specific binding to some unrelated antigens, raising considerable concerns over its potential clinical development. Here, we describe a phage display-based strategy to examine the effects of multiple mutations of IgG1 monomeric Fc and, simultaneously, to identify new Fc monomers with desired properties. Consequently, we identified a novel monomeric Fc that displayed significantly decreased non-specificity. In addition, it exhibited higher thermal stability and comparable pH-dependent FcRn binding to the previous reported monomeric Fc. These results provide baseline to understand the mechanism underlying the generation of soluble IgG1 Fc monomers and warrant the further clinical development of monomeric Fc-based fusion proteins as well as antigen binders.